Let’s Talk About Sex: The Impact of Partnership Contexts on Communication About HIV Serostatus and Condom Use Among Men Who Have Sex with Men (MSM) and Transgender Women (TW) in Lima, Peru - Ayer, Amrita (2021)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.